El Centro Nacional de Inteligencia: una aproximación a su régimen jurídico - Moret Millás, Vicente (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2005)
The new security challenges that the world faces today have the consequence that citizens ask answers to their governments. Hence, the article analyses different aspects related to the legal system of the National Intelligence Center (CNI) in Spain, as well as it makes a brief approach to the other organizations of the state that carry out the same functions. The article underlines the coordination between them as the key point to get the right levels or efficiency in the light of the experiences in other countries. Moreover, the text deals with subjects about the internal organization of the Center, according to its legal system, which are not very well known. Those subjects are very interesting from the point of view of maintaining the individual rights, as well as taking into account the administrative regulation in its organizational, financial or human resources management dimensions. Thus, the target is to give a whole view of the Center that ranges over various disciplines, in order to know, from the legal and administrative point of view, one of the obviously less known organizations of the State, whose tasks are nevertheless of vital importance to the country.